2018
DOI: 10.1038/s41598-017-18877-8
|View full text |Cite
|
Sign up to set email alerts
|

Low amounts of dietary fibre increase in vitro production of short-chain fatty acids without changing human colonic microbiota structure

Abstract: This study investigated the effect of various prebiotics (indigestible dextrin, α-cyclodextrin, and dextran) on human colonic microbiota at a dosage corresponding to a daily intake of 6 g of prebiotics per person (0.2% of dietary intake). We used an in vitro human colonic microbiota model based on batch fermentation starting from a faecal inoculum. Bacterial 16S rRNA gene sequence analysis showed that addition of 0.2% prebiotics did not change the diversity and composition of colonic microbiota. This finding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 45 publications
(46 reference statements)
3
64
1
Order By: Relevance
“…Previously, the KUHIMM in vitro human colonic microbiota model produced bacterial species numbers and diversity roughly equivalent to those in fecal samples from HS . Initially, the stability of the gut microbiota from four UC patients was monitored in the cultures of KUHIMM until 48 h after inoculation of fecal donors (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, the KUHIMM in vitro human colonic microbiota model produced bacterial species numbers and diversity roughly equivalent to those in fecal samples from HS . Initially, the stability of the gut microbiota from four UC patients was monitored in the cultures of KUHIMM until 48 h after inoculation of fecal donors (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…However, these models do not reflect the complex microbial diversity in UC fecal donors, as shifts in microbial diversity occur during successive culture in multicompartment reactors . We, therefore, developed an in vitro human colonic model using the batch fermentation system (named as the Kobe University Human Intestinal Microbiota Model [KUHIMM]), which simulates the bacterial proportions and diversity of fecal samples from healthy humans as confirmed by next‐generation sequencing (NGS) analysis . The anoxic condition in the KUHIMM was carefully constructed using the defined medium for the growth of anaerobes and constant flushing with anaerobic gas .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vegetables rich in insoluble fibres in the present study showed greater parameters of fermentation kinetics and higher SCFA production than those obtained for cellulose in an in vitro model. SCFA are recognised fermentation products of great importance for health, and which perform several functions, such as the regulation of absorption of water and minerals, the reduction of the pH of the colon thus inhibiting the development of pathogens present, while promoting the growth of beneficial bacteria (48) . Thus, it should be understood that, the relationships between fermentable carbohydrates and metabolic yield depend on the composition of the microbial community and the metabolic characteristics of each anaerobic bacterium (49) .…”
Section: Discussionmentioning
confidence: 99%